A Study of Classroom Teachers' Experiences in Mathematics Learning Management - Anisa Lutfiatun Zakiyah; Lumaurridlo; Sandi Aji Wahyu Utomo (Insight School Academy, 2023)
Introduction to The Problem : This study aims to obtain an overview of teachers' experience in managing classes in mathematics subjects in elementary schools. Purpose: From formulating the existing problems, the research objective is to obtain an overview of the teacher's experience in classroom management of mathematics subjects in elementary schools. Design/methods/approach: The form of research used is qualitative with a phenomenological research approach. The data collection techniques used were in-depth interviews and document studies. The instruments used in this research were interview guidelines and documentation study guidelines. Data validity was done through triangulation. The triangulation used in this research is source and method. The data analysis technique uses interactive analysis which consists of 3 stages, namely: reduction, data presentation, and conclusion drawing/verification. Findings: The results showed that 1) Learning resources used in the form of various kinds, including LKS, package books, the internet, teaching aids, and the natural environment, 2) Management of students, teachers always create good relationships with their students by giving freedom but still providing boundaries for behavior that can be done and not. Teachers also provide rewards or awards for students who behave positively; 3) In learning activities, it is pretty well done the way teachers create active and fun learning and can condition if there is a disturbance during learning; it is just that the use of learning methods is less varied, 4) Learning assessment is carried out with three aspects, knowledge, skills, and attitudes. Knowledge is obtained from daily grades, and PTS / PAS, skills are obtained from project results, portfolios, and work performance, while attitude assessment is obtained from direct observation. Research implications/limitations: The study has limitations in the scope of the respondents studied, which is limited to only one school. Research on a broader scope is needed to obtain a more detailed picture of some school quality characteristics, respondents' backgrounds, and other scopes. Originality/value: This is your opportunity to provide readers with an analysis of the value of your results. It is a good idea to ask colleagues whether your analysis is balanced and fair, and again, it is essential not to exaggerate. You can also conjecture what future research steps could be.